Crystal structure of Zika virus NS2B-NS3 protease in complex with a boronate inhibitor - Lei, Jian; Hansen, Guido; Nitsche, Christoph; Klein, Christian D.; Zhang, Linlin; Hilgenfeld, Rolf (Science, 2016)
Zooming in on the Zika virus protease - The lack of a vaccine or antiviral drugs to combat the Zika virus has scientists scrambling to identify and better characterize potential drug targets. One attractive candidate is the NS2B/NS3 viral protease, which, together with host cell proteases, cleaves the viral polyprotein into the individual proteins required for viral replication. Lei et al. report the crystal structure of this protease bound to a peptido-mimetic inhibitor. The structure reveals key interactions that probably contribute to the high catalytic efficiency of this enzyme relative to other flaviviruses, indicating promising starting points for drug design. - Science, this issue p. 503 - The ongoing Zika virus (ZIKV) outbreak is linked to severe neurological disorders. ZIKV relies on its NS2B/NS3 protease for polyprotein processing; hence, this enzyme is an attractive drug target. The 2.7 angstrom; crystal structure of ZIKV protease in complex with a peptidomimetic boronic acid inhibitor reveals a cyclic diester between the boronic acid and glycerol. The P2 4-aminomethylphenylalanine moiety of the inhibitor forms a salt-bridge with the nonconserved Asp83 of NS2B; ion-pairing between Asp83 and the P2 residue of the substrate likely accounts for the enzyme’s high catalytic efficiency. The unusual dimer of the ZIKV protease:inhibitor complex seen in the crystal may provide a model for assemblies formed at high local concentrations of protease at the endoplasmatic reticulum membrane, the site of polyprotein processing. - Analysis of Zika virus protease bound to a peptidomimetic inhibitor reveals its catalytic efficiency and promise as a drug target. - Analysis of Zika virus protease bound to a peptidomimetic inhibitor reveals its catalytic efficiency and promise as a drug target.